Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd001871.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing obesity in children

Abstract: Background Obesity prevention is an international public health priority. The prevalence of obesity and overweight is increasing in child populations throughout the world, impacting on short and long-term health. Obesity prevention strategies for children can change behaviour but efficacy in terms of preventing obesity remains poorly understood. Objectives To assess the effectiveness of interventions designed to prevent obesity in childhood through diet, physical activity and/or lifestyle and social support. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
909
0
71

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(999 citation statements)
references
References 90 publications
16
909
0
71
Order By: Relevance
“…60 Another systematic review examining interventions for childhood obesity prevention also reported that the majority of studies reviewed did not have a significant impact. 22 These results suggest that the demonstration of weight loss among overweight children may be more easily attainable than the demonstration of the prevention of weight gain. As noted above, this review combined intervention and prevention studies, as the strategies used are substantially the same in both cases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…60 Another systematic review examining interventions for childhood obesity prevention also reported that the majority of studies reviewed did not have a significant impact. 22 These results suggest that the demonstration of weight loss among overweight children may be more easily attainable than the demonstration of the prevention of weight gain. As noted above, this review combined intervention and prevention studies, as the strategies used are substantially the same in both cases.…”
Section: Discussionmentioning
confidence: 95%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] With the exception of one recent review 20 and an earlier review conducted by our team in collaboration with the Community Guide Branch of the Center for Disease Control and Prevention (CDC), 25 this work is unique in that it focuses specifically on studies undertaken in schools. Previous reviews have focused solely on the prevention of obesity 22 or weight loss interventions among already overweight children. 23 Recognizing that the strategies to prevent unnecessary weight gain and to treat obesity in children overlap considerably, this review includes studies with both aims.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The achieved weight loss and its maintenance were more pronounced and most importantly sustained as compared to previous studies. [11][12][13][14] Apart from differences in age, race and degree of overweight, this finding can probably be explained Four-year follow-up after intervention T Reinehr et al in part by proving the motivation at the beginning of the intervention using criteria, which have been reported to be predictive for success. 4 Furthermore, the combination of individual care and group sessions, the intensive education of parents and the graduated structure of the intervention might be factors leading to long-term success.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, given the paucity of studies where the intervention and/or follow-up phases lasted for a minimum of 1 year, shorter term studies have also been included in many reviews, e.g. Summerbell et al 24 and Doak et al 30 In contrast to the earlier reviews in which methodological rigour was the main yardstick by which intervention studies were appraised, more recent reviews have intentionally been more inclusive and diverse in their appraisal process in order to identify elements of best practice for the prevention of obesity at the population level 24,30,31 . Without doubt, the most comprehensive and inclusive synthesis of the literature to date has been the one carried out by Flynn et al 31 in which 500 reports were evaluated not only for their methodological rigour, but also for programme development/evaluation and the degree to which they encompassed the principles of population health and immigrant health.…”
Section: Introductionmentioning
confidence: 99%